2020
DOI: 10.1002/jpen.2018
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Gastrostomy Tube Placement in Patients with Advanced Amyotrophic Lateral Sclerosis With Noninvasive Ventilation

Abstract: Background In patients with amyotrophic lateral sclerosis (ALS), bulbar muscle dysfunction can occur, which eventually requires the initiation of enteral tube feeding. However, there is no consensus on the optimal timing for the gastrostomy or the proper ventilator support method during the procedure. We aimed to investigate the safe range of gastrostomy according to respiratory support status and forced vital capacity (FVC) % of predicted values classification and to compare the safety of noninvasive and inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The notion of determining suitability for gastrostomy on a pulmonary function threshold alone is coming into question. Whilst the NICE guidance is clear that FVC should be >50% of predicted to perform the procedure safely [9], Kim et al reported outcomes suggesting that gastrostomy insertion can be performed safely in patients with a FVC <30%, irrespective of ventilatory support [14 ▪ ]. These findings may be interpreted with caution given contradictory findings about mortality risk in NIV dependent individuals observed in contemporaneous studies, but does suggest that the relationship between NIV use, pulmonary function and survival post gastrostomy may not be as linear as initially thought.…”
Section: Prognosismentioning
confidence: 99%
“…The notion of determining suitability for gastrostomy on a pulmonary function threshold alone is coming into question. Whilst the NICE guidance is clear that FVC should be >50% of predicted to perform the procedure safely [9], Kim et al reported outcomes suggesting that gastrostomy insertion can be performed safely in patients with a FVC <30%, irrespective of ventilatory support [14 ▪ ]. These findings may be interpreted with caution given contradictory findings about mortality risk in NIV dependent individuals observed in contemporaneous studies, but does suggest that the relationship between NIV use, pulmonary function and survival post gastrostomy may not be as linear as initially thought.…”
Section: Prognosismentioning
confidence: 99%